Cough in Idiopathic Pulmonary Fibrosis - Mann, Jennifer; Goh, Nicole S. L.; Holland, Anne E.; Khor, Yet Hong (Frontiers in Rehabilitation Sciences, 2021)
Chronic cough is experienced by most patients with idiopathic pulmonary fibrosis (IPF). It is often the first symptom and is associated with reduced quality of life, increased rates of depression and anxiety, more severe physiological impairment, and disease progression. Although not fully understood, recent gains in understanding the pathophysiology of chronic cough in IPF have been made. The pathophysiology is likely multifactorial and includes alterations in mucous production and clearance, architectural distortion, and increased cough reflex sensitivity, suggesting a role for targeted therapies and multidisciplinary treatment. Modifiable comorbidities can also induce cough in patients with IPF. There is a renewed emphasis on measuring cough in IPF, with clinical trials of novel and repurposed therapies for chronic cough emerging in this population . This review provides an update on the clinical characteristics, pathophysiology, and measurement of chronic cough in patients with IPF and summarizes recent developments in non-pharmacological and pharmacological therapies.